2012
DOI: 10.2135/cropsci2011.09.0526
|View full text |Cite
|
Sign up to set email alerts
|

Response of Potato Gas Exchange and Productivity to Phosphorus Deficiency and Carbon Dioxide Enrichment

Abstract: The degree to which crops respond to atmospheric COg enrichment may be influenced by nutrition. To determine the extent to which dry matter production, canopy and leaf photosynthesis, and transpiration are influenced by P and COg, potatoes [Solanum tuberosum L. cultivar Kennebec) were grown in outdoor soilplant-atmosphere research (SPAR) chambers at two levels of COg (400 or 800 pmol moh^) and three levels of P fertilization. Total dry matter declined an average 42% between high and low P fertilizer and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
17
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 52 publications
9
17
1
2
Order By: Relevance
“…Tissue P and N concentration followed nearly a similar trend for both the uppermost fully expanded leaves and in the whole-plant or whole-plant leaves. The observed decrease (P) or increase (N) in the tissue nutrient concentration under Pi deficiency has also been reported in other studies (Fleisher et al 2012;Singh, Badgujar, Reddy, Fleisher & Timlin 2013). Apparently, due to Pi deficiency the tissue P concentration decreased in greater proportion than the plant biomass leading to markedly increased PUE.…”
Section: Tissue Constituentssupporting
confidence: 85%
See 1 more Smart Citation
“…Tissue P and N concentration followed nearly a similar trend for both the uppermost fully expanded leaves and in the whole-plant or whole-plant leaves. The observed decrease (P) or increase (N) in the tissue nutrient concentration under Pi deficiency has also been reported in other studies (Fleisher et al 2012;Singh, Badgujar, Reddy, Fleisher & Timlin 2013). Apparently, due to Pi deficiency the tissue P concentration decreased in greater proportion than the plant biomass leading to markedly increased PUE.…”
Section: Tissue Constituentssupporting
confidence: 85%
“…Previous studies suggested that Pi deficiency and eCO 2 may also alter the nutrient dynamics and biomass partitioning in the plant organs and affect the assimilation of other nutrients such as nitrogen (Israel et al 1990;Rufty et al 1991;Reddy & Zhao 2005;Fleisher et al 2012;Singh, Badgujar, Reddy, Fleisher & Timlin 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tuber yield of all cultivars under low P level was on average 32.4% lower than under high P level, indicating that significant reductions in tuber yield occur when potato plants are grown under P-limiting conditions (Alvarez-Sánchez et al 1999;Dechassa et al 2003;Fleisher et al 2012). In the two P levels, the cultivars Mondial and Agata showed the greatest tuber yield compared with the other cultivars ( Low P High P Low P High P Low P High P Low P High P Low P High P Dry matter partitioning (%) .…”
Section: Resultsmentioning
confidence: 97%
“…biochemical model of C 4 photosynthesis (von Caemmerer and Furbank, 1999). Fleisher et al (2012) addressed P deficiency in potato by modifying V cMax (maximum rate of rubisco carboxylation), J (electron transport rate), and TPU (trios-phosphate utilization). Jacob and Lawlor (1992) found less ribulose-1,5-bisphosphate (RuBisCO) in P-deficient maize but did not find decreased activity.…”
Section: Source Of Variationmentioning
confidence: 99%